'Outdooring' the Historical Corpus of English in Ghana: Insights from the compilation of a historical corpus of New English. Issue 2 (30th January 2018) - Brato, Thorsten
Abstract : Over the last 30 years there has been an upsurge in research and theorising on postcolonial Englishes. Beginning with Kachru's (1985) Three Circles model, more recently the focus has shifted to models focusing on identity construction and historical developments (Schneider, 2007), central and peripheral varieties and their spheres of influence (Mair, 2013), and those aiming to provide a more integrated approach to postcolonial and non-postcolonial Englishes (Buschfeld & Kautzsch, 2017). Dedicated corpora such as the International Corpus of English (ICE; Greenbaum, 1991) and the Corpus of Global Web-based English (GloWbe; Davies & Fuchs, 2015) have been designed to allow for a synchronic comparison of Englishes around the world and have since been widely used to study variation on the different levels of linguistic description within and across varieties. Recently, ICE corpora have also been used to test assumptions laid out by Schneider (2007), e.g. by comparing data from ICE corpora of varieties which have progressed to different phases (Mukherjee & Gries, 2009) or by taking an apparent-time approach to test developments within one variety (Fuchs & Gut, 2015).